2011
DOI: 10.1371/journal.pone.0026082
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Cells in Murine Colitis: Multi-Signal Analysis Confirms Pericryptal Myofibroblast Engraftment without Epithelial Involvement

Abstract: BackgroundThe contribution of bone marrow-derived cells to epithelial tissues in the inflamed gut remains controversial. Recent reports have suggested that cell fusion between bone marrow-derived cells and the intestinal epithelium takes place in inflammatory conditions.MethodsIn attempts to confirm this, we have undertaken gender mis-matched bone marrow (BM) transplants from male Swiss Webster (SWR) mice to B and T cell-deficient female Rag2 KO mice which, 4 weeks later, were given 5% dextran sodium sulphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Susceptibly of DSS to induce colitis differs amongst different mouse strains [24,25]. Therefore, we used 3% DSS in our experiments with C57BL/6J based on our previous work [8,19], and 5% DSS [26] for the germ free mouse experiment. The animals were weighed daily and colonic length measurements were performed at the end of the experiments following CO 2 asphyxiation.…”
Section: Methodsmentioning
confidence: 99%
“…Susceptibly of DSS to induce colitis differs amongst different mouse strains [24,25]. Therefore, we used 3% DSS in our experiments with C57BL/6J based on our previous work [8,19], and 5% DSS [26] for the germ free mouse experiment. The animals were weighed daily and colonic length measurements were performed at the end of the experiments following CO 2 asphyxiation.…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow-derived cells contributing to the (myo)fibroblast population in the stomach, small intestine, and colon of rats and mice were shown in all seven included studies [ 5 , 32 , 33 , 34 , 35 , 36 , 37 ]. Lee et al [ 37 ] observed pericryptal engraftment in the stomach but no epithelial engraftment. Several models of inflammation/damage induction reported an increase in engrafted (myo)fibroblasts in gastrointestinal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…The fate of bone marrow derived cells migrated to colons during colitis is an active and controversial area of research. After bone marrow transplantation and induction of murine colitis, it is likely that some of bone marrow derived cells exist as lymphoid cells and myofibroblasts in the colons 5 . Another report suggested that bone marrow derived cells serve as endothelial progenitor cells for neovascularization in recovery process 6 .…”
Section: Discussionmentioning
confidence: 99%